Linguistic landscape of culinary businesses in Palopo - Masruddin, Masruddin; Amelia, Amelia; Ajma, St. Annazila Cahyani; Thayyib, Magfirah (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This study investigates the linguistic landscape of the culinary business in Palopo Town, South Sulawesi Province, Indonesia, addressing the limited research on smaller urban contexts with distinct local languages and commercial dynamics. The research aims to identify the most frequently used languages in culinary signboards and to explore the motivations behind these linguistic choices. Employing a qualitative approach, data were collected through field observation in October 2025, resulting in 20 photographed culinary signboards. The analysis used the interactive model, involving data reduction, categorization based on language composition and communicative function, and sociolinguistic interpretation. The findings reveal four categories: monolingual English (40%), monolingual Indonesian or local languages (30%), bilingual (15%), and multilingual (5%). English is predominantly associated with modernity and global identity, while Indonesian and local languages signal cultural closeness and authenticity. Most business names are non-clausal nominal phrases, emphasizing brevity and branding efficiency. The results demonstrate that language choice in Palopo’s culinary signage functions not only as identification but also as a strategic tool for identity representation, market positioning, and negotiation between global and local values in public space.